Natural history of the Pulau Tioman group of islands - Phang, Siew Moi; Affendi Yang Amri; Ooi, Jillian Lean Sim; Abdul Jamal Mydin (Monograph series (Universiti Malaya. Institute of Ocean and Earth Sciences), 2008)
A workshop "Marine Natural History of the Tioman Park Group of Islands" was held in 2006, on Pulau Tioman in conjuction with the signing of the Memorandum of Understanding between the Institute of Ocean and Earth Sciences and the launch of the Pulau Tioman Marine Research Station. This monograph comprises paper presented at the workshop as well as biodiversity checklists of terrestrial, freshwater and marine flora and fauna compiled from published reports.